2022
DOI: 10.3389/fmed.2022.948842
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of S gene characteristic sequences and changes in properties of protein expression in HBV ASCs with low-level HBsAg

Abstract: ObjectiveWe detected the serum HBsAg immune complex (HBsAg-CIC) and sequenced the HBV S gene in these patients to reveal the association between sustained low-level expression of HBsAg and mutated S gene sequence characteristics, protein function changes, and HBsAg immune complex formation.MethodsA total of 204 samples were collected and divided into high-level (n = 60, HBsAg level >10 IU/ml) and low-level (n = 144, HBsAg level ≤ 10 IU/ml) HBsAg groups. The clinical and epidemiological data of the two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…HBVr can occur during immunosuppression in patients with chronic hepatitis B (anti-HBc-positive and HBsAg positive) or resolved infection (anti-HBc-positive and HBsAg negative) [ 28 , 29 ]. Liu et al [ 30 ] found that the occurrence of HBVr in HCC patients after HAIC was 11.7% (16/137) in the antiviral group and 27.3% (9/33) in the non-antiviral group.…”
Section: Discussionmentioning
confidence: 99%
“…HBVr can occur during immunosuppression in patients with chronic hepatitis B (anti-HBc-positive and HBsAg positive) or resolved infection (anti-HBc-positive and HBsAg negative) [ 28 , 29 ]. Liu et al [ 30 ] found that the occurrence of HBVr in HCC patients after HAIC was 11.7% (16/137) in the antiviral group and 27.3% (9/33) in the non-antiviral group.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who tested negative for HBV pgRNA at the time of HBsAg loss had low baseline HBV DNA and HBsAg levels, as well as low HBV replication levels.Considering the potential association between HBV pgRNA and viral replication, this study suggests that HBsAg loss should not be the sole criterion for evaluating a functional cure in HIV/HBV coinfection. Owing to the unique immune status of HIV patients and the strong antiviral effects of ART, HBsAg in HIV/HBV-co-infected individuals may undergo mutations, making it difficult to detect or produce nonsecretory HBsAg using existing testing methods 15. HBsAg loss is not a comprehensive indicator of HBV functional cure in HIV/HBV-co-infected individuals.…”
mentioning
confidence: 99%